Bionetworking and Strategic Linking between India and Japan: How Clinical Stem Cell Intervention Continues despite New Regulatory Guidelines. Issue 3 (1st September 2017) - Patra, Prasanna Kumar; Sleeboom-Faulkner, Margaret
Abstract : Based on a case study of a clinical stem cell intervention (CSCI) center in Chennai, India, this article explores distinct entrepreneurial strategies for the promotion of unrecognized clinical stem cell applications in India. It shows that the center—an Indo-Japanese joint-venture—is able to promote the CSCI due to its central position in a network relationship, its possession of specialized skills and knowledge, and its ability to maneuver other actors in the network and to identify and utilize their latent value. We examine the developmental history of the making and remaking of regulation and the shift in the way clinical stem cell application providers function—from institutional embedment to strategic linking through collaborative networks. We ask why and how unauthorized clinical applications are sustained and promoted in India. We conclude that this is possible as a result of a number of factors: jurisdictional ambiguity, institutional inability, issues concerning the legal enforceability of the relevant guidelines, the complexity of the collaborative network structure that facilitates the circumvention of the regulation, and the nonfunctioning of apex-level committees.